A decent work framework: women in the ICT sector in India. (November 2016) - Mehta, Balwant Singh
It is argued that the ICT sector offers greater ease of access to employment for women than traditional sectors. This is reflected in the high representation of women employees in the ICT sector in India. Considering the importance of the ICT sector in India, policy makers and industry leaders are continuously debating on women's work and working conditions in this sector. In this paper an attempt has been made to understand the critical issue by using a modified version of the decent work framework and discussing both favourable and unfavourable results of women's employment in the Indian ICT sector.